Moon Hooch [compact disc] (Hornblow Recordings : Palmetto Records, 2013)
Recorded in just a single day, their debut record, Moon Hooch, gives the listener a taste of what's to come for these guys. They seamlessly blend house, dubstep, drum & bass, and jazz into a style that is uniquely Moon Hooch: cave music.